Treatment options after virological failure of first-line tenofovir-based regimens in South Africa: an analysis by deep sequencing. (24th April 2016) - Casadellà, Maria; Noguera-Julian, Marc; Sunpath, Henry; Gordon, Michelle; Rodriguez, Cristina; Parera, Mariona; Kuritzkes, Daniel R.; Marconi, Vincent C.; Paredes, Roger
Abstract : In a South African cohort of participants living with HIV developing virological failure on first-line tenofovir disoproxyl fumarate (TDF)-based regimens, at least 70% of participants demonstrated TDF resistance according to combined Sanger and MiSeq genotyping. Sanger sequencing missed the K65R mutation in 30% of samples. Unless HIV genotyping is available to closely monitor epidemiological HIV resistance to TDF, its efficacy as second-line therapy will be greatly compromised.